Korekcija refrakcijskih napak - Pfeifer, Vladimir (Zdravniški vestnik, 2005)
Background. Spectacles and contact lenses are the most frequently used, the safest and the cheapest way to correct reftractive errors. The development of keratorefractive surgery has brought new opportunities for correction of refractive errors in patients who have the need to be less dependent of spectacles or contact lenses. Until recently, RK was the most commonly performed refractive procedure for nearsighted patients. Conclusions. The introduction of excimer laser in refractive surgery has given the new opportunities of remodelling the cornea. The laser energy can be delivered on the stromal surface like in PRK or deeper on the corneal stroma by means of lamellar surgery. In LASIK flap is screated with microkeratome in LASEK with ethanol and in epi-LASIK the ultra thin flap is created mechanically.
Keywords: Astigmatism; Astigmatizem; Hiperopija; Hyperopia; Keratotomija radialna; Keratotomy, Radial; kirurško zdravljenje; Laser Surgery; Laserska kirurgija; Miopija; Myopia; napake; oftalmologija; oko; Refractive Errors; refrakcija; Refrakcijske motnje; Surgery; vid